Optical and Photolumenance Studies of Deposited CuO2 Nano-Structures at Different Laser Energies Effects - Fakhri, Makram A.; Alsultany, Forat Hamzah; Wahid, M.H.A.; Alghurabi, Milad Nazar Abdul Kareem (Diffusion and defect data. Solid state data. Pt. A, Defect and diffusion forum, 2022)
The deposition of copper oxide utilizing a pulsed laser deposition technique employing a reactive pulsed laser as a deposition technique is the subject of this study (RPLD), 1064 nm, 10 Nanosecond Q-switch Nd-YAG laser with 350 °C, and 800-1200 mJ energies of laser was used to deposited a high purity target of Cupper and deposited on the quartz substrates synthesized and study the laser energies effect on the optical and photoluminescence properties.